2017
DOI: 10.15835/nsb9310091
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Fluorescence Reaction of Four Rice Genotypes to Exogenous Application of IAA and Kinetin under Drought Stress

Abstract: To assess the effects of IAA and Kinetin plant growth regulators in order to improve the drought tolerance in rice seedlings (Oryza sativa L.), a factorial experiment was carried out based on complete randomized design with three replications. The experimental factors included different rice genotypes ['Gharib', 'Khazar',], drought stress from 1 to 4 code of the Vergara coding system and control (normal irrigation) and growth regulators in three levels (IAA and Kinetin through foliar spraying and non-applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Accordingly, Bagheri et al (2019) reported an increase in the number of leaves and yield components of wheat by priming with indole acetic acid (IAA), an auxin precusor compound. Similarly, Salehifar et al (2017) also reported a higher growth rate and DT in rice genotypes treated with IAA. In tobacco, auxin was shown to facilitate lateral root growth development under DS (Wang et al, 2018).…”
Section: Phytohormones: Important Plant Mediators To Cope With Drought Stressmentioning
confidence: 80%
“…Accordingly, Bagheri et al (2019) reported an increase in the number of leaves and yield components of wheat by priming with indole acetic acid (IAA), an auxin precusor compound. Similarly, Salehifar et al (2017) also reported a higher growth rate and DT in rice genotypes treated with IAA. In tobacco, auxin was shown to facilitate lateral root growth development under DS (Wang et al, 2018).…”
Section: Phytohormones: Important Plant Mediators To Cope With Drought Stressmentioning
confidence: 80%
“…Four plant hormones were used, and the characteristics of each active ingredient sprayed in this study are mentioned in Supplementary Table 1. The concentrations of the foliar growth regulators used were as follows: (i) auxins (1-Naphthaleneacetic acid: NAA) at 5 × 10 −5 M; (ii) gibberellins (Gibberellic acid: GA3) at 5 × 10 −5 M; (iii) cytokinins (Trans-Zeatin) at 1 × 10 −5 M; and (iv) brassinosteroids [Spirostan-6-one, 3,5-dihydroxy-, (3b,5a,25R)] at 5 × 10 −5 M. These concentrations were selected since they showed a positive response and increased plant tolerance to heat stress (Zahir et al, 2001;Wen et al, 2010;El-Bassiony et al, 2012;Salehifar et al, 2017). Rice plants without any plant growth regulator sprays were only treated with distilled water.…”
Section: Heat Stress and Plant Hormone Treatmentsmentioning
confidence: 99%
“…Numerous studies have been established to illustrate the production of tissue culture from either the basal stem [9] and fruit [1,11] utilizing various PGRs such as 6-benzylaminopurine (BAP), 2, 4-Dichlorophenoxyacetic acid (2,4-D) and KN related to multipurpose benefits from sugar palm. The current study therefore uses a mixture of KN and IAA as PGRs to evaluate the growth of sugar palm from fruit as an explant.…”
Section: Resultsmentioning
confidence: 99%
“…The study indicated that pigeon pea treated with IAA 10mm in pre-treatment (87.67±0.33 cm) had a significance difference with respect to control (68.00±0.58 cm) in terms of plant height [8]. Another studies on application of KN and IAA in a field study to improve the drought stress tolerance in four rice genotypes (Gharib', 'Khazar', 'Sepidrood' and 'IR83750-131-1'('IR83750')) showed manipulation of amount used for IAA and KN are vital in developing the optimum drought tolerance ratio where highest percentage of relative water content (RWC) in "Sepidrood" (51.26% and 50.19% treated in IAA and KN respectively) and lowest electrolyte leakage (EL) with (25.79% and 27.59% treated in IAA and KN respectively) [9]. Hence, the aim of this study is to determine the optimum combination of KN and IAA on sugar palm culture and the response towards the hormone combination.…”
Section: Introductionmentioning
confidence: 99%